(untitled) (Journal of Informatics Education and Research, 2025)
The core objective of the study is to determine the impact of strategic human resource management on environmental performance. The authors studied the relationship between strategic human resource management, internal environmental concern, organizational citizenship behavior for the environment, and environmental performance. The study made three main contributions. They are it linked EM and HRM in order to better understand how firms are able to achieve environmental performance. It is noted that ‘‘the topic of environmental sustainability” is not reflected in the research agendas of most areas of management scholarship. By providing original data, this study helps to fill this gap, it formulated clear and specific relation between the roles played by frontline employees’ and environmental performance and identified the influence of managers as one factor to implement the regulations concerned with environmental performance. In the study, it is assured that managers can play an active role. In particular, internal environment orientation was identified as possible moderating variable in the relationship between SHRM and pro-environmental behavior at work. The research is highly significant because of the above reasons and contributed new concept about the clear relationship between human resource management and environmental performance.